Local arterial stiffness measured by ultrafast ultrasound imaging in childhood cancer survivors treated with anthracyclines - Rasouli, Rahna; Baranger, Jerome; Slorach, Cameron; Hui, Wei; Venet, Maelys; Nguyen, Minh B.; Henry, Matthew; Gopaul, Josh; Nathan, Paul C.; Mertens, Luc; Villemain, Olivier (Frontiers in Cardiovascular Medicine, 2023)
Background There is conflicting literature regarding the long-term effect of anthracycline treatment on arterial stiffness. This study assessed local arterial stiffness using ultrafast ultrasound imaging (UUI) in anthracycline treated childhood cancer survivors, at rest and during exercise. Methods 20 childhood cancer survivors (mean age 21.02 ± 9.45 years) treated with anthracyclines (mean cumulative dose 200.7 ± 126.80 mg/m2) and 21 healthy controls (mean age 26.00 ± 8.91 years) were included. Participants completed a demographic survey, fasting bloodwork for cardiovascular biomarkers, and performed a submaximal exercise test on a semi-supine bicycle. Pulse wave velocity (PWV) was measured in the left common carotid artery by direct pulse wave imaging using UUI at rest and submaximal exercise. Both PWV at the systolic foot (PWV-SF) and dicrotic notch (PWV-DN) were measured. Central (carotid-femoral) PWV was obtained by applanation tonometry. Carotid measurements were taken by conventional ultrasound. Measures were compared using two-tailed Students t-test or Chi-squared test, as appropriate. Results There was no statistically significant difference (p > 0.05) between childhood cancer survivors and healthy controls in demographic parameters (age, sex, weight, height, BMI), blood biomarkers (total cholesterol, triglycerides, LDL-c, HDL-c, hs-CRP, fasting glucose, insulin, Hb A1c), cardiovascular parameters (intima media thickness, systolic and diastolic blood pressure, heart rate, carotid diameters, distensibility) or PWV measured by UUI at rest or at exercise. There was also no difference in the cardiovascular adaptation between rest and exercise in the two groups (p > 0.05). Multivariate analysis revealed age (p = 0.024) and LDL-c (p = 0.019) to be significant correlates of PWV-SF in childhood cancer survivors, in line with previously published data. Conclusion We did not identify a significant impact of anthracycline treatment in young survivors of childhood cancer on local arterial stiffness in the left common carotid artery as measured by UUI.